Human Resource Development: Overview of the Performance Evaluation and Performance Appraisal viewpoints - Navia Thuy; Elly Trinh (Journal La Bisecoman, 2020)
This article discusses Human Resource Development by reviewing Performance Evaluation and Performance Appraisals. Every organization must prepare a program that contains activities that can improve the capabilities and professionalism of HR so that the organization can survive and develop in accordance with the organizational environment. The appraisal process starts from setting employee performance standards. A manager must determine what achievements, skills or outputs will be evaluated. These performance standards should be included in the job analysis and job description. After the performance standards have been set, the next thing to do is communicate to each employee, so that the employees know what is expected by the company. Performance appraisals are used to tell employees how far they are performing and the rewards they will get. Performance appraisal also aims to evaluate and provide feedback to employees that will develop employees and also the effectiveness of the organization. Poor performance shows the need for training as well as good performance can reflect the great potential that must be developed.